Pelatihan Literasi Digital Bagi Guru di Pondok Pesantren Al-Marjan Mulabaru Lebak Banten - Mutmainah, Isbandriyati; Yulia, Iis Anisa; Susanto, Heri; Rumna; Pranamulia, Agus; Fitrianti, Dewi; Putra, Mulyana Gustira; Arifien, Yunus; Maad, Faizal; Fitriani, Anna; Solihin, Lalu; Marnilin, Feni; Sukayat, Harmoko; Widjaja, Ichwan Rachmanu; Wahidhani, Eha Hasni; Rusman, Hedar; Irawan, Rahmat; Mahfudi, Ahmad Zaid (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
Islamic boarding schools as Islamic educational institutions in Indonesia have an important role in producing a young generation with noble character, religious knowledge and ready to face the challenges of the times. Islamic boarding schools must quickly respond positively and adapt to changes that occur. Islamic boarding schools as educational institutions currently need to prepare teachers who are competent in accordance with the needs of the times. Digital literacy is one of the competencies that is quite important in meeting the knowledge needs of students. Digital literacy training is carried out to prepare teachers who are in line with educational needs in the era of industrial revolution 4.0 but cannot be separated from the teachings of the Islamic religion. With good digital literacy, teachers at Islamic boarding schools can access wider and more up-to-date information, increase the effectiveness of teaching and learning, and utilize digital media for learning activities, da'wah and spreading Islamic values. Therefore, digital literacy training is needed for teachers at the Al-Marjan Mulabaru Islamic Boarding School, Lebak Banten. The aim of this community service activity is to increase the knowledge and skills capacity of teachers at the Al-Marjan Mulabaru Islamic Boarding School in Lebak Banten regarding digital literacy. The result of this activity is that teachers at the Al-Marjan Mulabaru Islamic Boarding School in Lebak Banten are able to understand digital literacy and show that teachers are able to have basic skills in using computers and the internet. The success of this training shows that teachers have high interest in digital literacy in Islamic boarding schools.